2016
DOI: 10.1515/sab-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Clubroot – An Emerging Disease Faced by Czech Oilseed Rape Growers

Abstract: Clubroot is caused by the pathogen Plasmodiophora brassicae Woronin and has become a serious problem in oilseed rape production in the Czech Republic. The disease was previously widespread in commercial vegetable production and in hobby gardens. Whereas previously restricted only to the NE, since 2010 oilseed rape clubroot has been spreading across the whole country. A five-year monitoring of clubroot occurrence based on disease symptoms detection on oilseed rape fields was accomplished by the Union of Oilseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Inoculum used for testing of the resistance to clubroot was composed by the most aggressive pathotypes P. brassicae within the Czech Republic. Clubs for inoculum preparation were collected from the hardest hit areas affected by clubroot near Svetla Hora in the Moravian-Silesian Region (Ricarova et al 2016). According to the identification method called the ECD (European Clubroot Differential set) Buczacki et al (1975), the pathogen was identified as pathotypes 17/31/31.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculum used for testing of the resistance to clubroot was composed by the most aggressive pathotypes P. brassicae within the Czech Republic. Clubs for inoculum preparation were collected from the hardest hit areas affected by clubroot near Svetla Hora in the Moravian-Silesian Region (Ricarova et al 2016). According to the identification method called the ECD (European Clubroot Differential set) Buczacki et al (1975), the pathogen was identified as pathotypes 17/31/31.…”
Section: Methodsmentioning
confidence: 99%
“…Seven different pathotypes have been revealed in the Czech Republic. The most common pathotypes are 7 (43%) and 6 (29%) (Ricarova et al 2016). Other systems distinguishing pathotypes are the European clubroot differential (ECD) set (Buczacki et al 1975) and the differential system of Some et al (1996).…”
Section: Introductionmentioning
confidence: 99%